Carcinoembryonic antigen has prognostic value for tumor downstaging and recurrence in rectal cancer after preoperative chemoradiotherapy and curative surgery: A multi-institutional and case-matched control study of KROG 14-12. Issue 2 (August 2015) - Lee, Jong Hoon; Kim, Dae Yong; Kim, Sung Hwan; Cho, Hyeon Min; Shim, Byoung Yong; Kim, Tae Hyun; Kim, Sun Young; Baek, Ji Yeon; Oh, Jae Hwan; Nam, Taek Keun; Yoon, Mee Sun; Jeong, Jae Uk; et al.
Abstract: Background and purpose: The Korean Radiation Oncology Group evaluated the significance of carcinoembryonic antigen (CEA) levels both as a predictor of tumor response after CRT and as a prognosticator for recurrence-free survival. Methods and materials: 1804 rectal cancer patients, staged cT3–4N0–2M0, participated in a multicenter study. The patients were administered preoperative radiation of 50.4 Gy in 28 fractions with 5-FU or capecitabine, followed by total mesorectal excision. Patients with elevated CEA levels (>5 ng/mL) were matched at a 1 ( n = 595):1 ( n = 595) ratio with patients with normal CEA (⩽5 ng/mL). The tumor response after CRT and the recurrence-free survival (RFS) rates were evaluated and compared between two arms. Results: An elevated CEA level ( p < 0.001) was determined to be a significant negative predictor of downstaging after CRT. The downstaging rate was 42.9% for normal CEA and 23.4% for elevated CEA. A multivariate analysis also revealed that cT ( p = 0.021) and cN classification ( p = 0.001), tumor size ( p = 0.002), and tumor location from the anal verge ( p = 0.006) were significant predictors for tumor downstaging. The 5-year RFS rates were significantly higher for the normal CEA arm than for the elevated CEA arm (74.2 vs. 63.5%, p < 0.001). Conclusions: Elevated CEA (>5 ng/mL) is a negative predictor of tumor downstaging after CRT and also has a negative impact on RFS in rectal cancer.